Variable left ventricular activation pattern in patients with heart failure and left bundle branch block. Issue 1 (15th December 2003) - Fung, J W-H; Yu, C-M; Yip, G; Zhang, Y; Chan, H; Kum, C-C; Sanderson, J E
Abstract : Objective: To determine the left ventricular (LV) activation pattern in patients with chronic heart failure and left bundle branch block (LBBB) on ECG. Design: Prospective study. Setting: Tertiary cardiology referral centre in Hong Kong. Patients: Seven patients with LV ejection fraction < 35% and typical LBBB on ECG with QRS duration ⩾ 130 ms were recruited. Five of them had non-ischaemic dilated cardiomyopathy. Methods: Non-contact mapping was used to investigate the LV global activation sequences. Tissue Doppler imaging was performed with the LV mapping and correlated with the activation sequences. Results: Three patients had preserved left bundle activation despite LBBB on ECG. Conduction block was detected in four patients during LV activation and the other three had homogeneous depolarisation propagation within the left ventricle. The latest segment of activation was located in either the lateral or the posterior region. Tissue Doppler imaging correlated well with non-contact mapping to locate the conduction block and the latest segment of activation. Conclusions: LV endocardial activation sequences in patients with chronic heart failure and LBBB are variable. This may have implications for patient selection for treatment with cardiac resynchronisation.